2011
DOI: 10.1258/ijsa.2011.010496
|View full text |Cite
|
Sign up to set email alerts
|

Survival of HIV-infected patients admitted to the intensive care unit in the era of highly active antiretroviral therapy

Abstract: We retrospectively studied outcomes for HIV-infected patients admitted to the intensive care unit (ICU) between January 1999 and June 2009. Patient demographics, receipt of highly active antiretroviral therapy (HAART), reason for ICU admission and survival to ICU and hospital discharge were recorded. Comparison was made against outcomes for general medical patients contemporaneously admitted to the same ICU. One hundred and ninety-two HIV-infected patients had 222 ICU admissions; 116 patients required mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 34 publications
(62 reference statements)
8
61
1
2
Order By: Relevance
“…Despite this and similar to prior studies, CD4 count and PVL were not independently associated with short-term mortality [3, 9, 2730]. Instead, acute illness severity was strongly associated with mortality in our study, an effect which has been demonstrated in several other studies [6, 9, 3133]. …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Despite this and similar to prior studies, CD4 count and PVL were not independently associated with short-term mortality [3, 9, 2730]. Instead, acute illness severity was strongly associated with mortality in our study, an effect which has been demonstrated in several other studies [6, 9, 3133]. …”
Section: Discussionsupporting
confidence: 73%
“…Several retrospective studies have had similar findings [5, 13, 27, 30, 34, 35]. Only two recent studies demonstrated a survival benefit with cART [6, 9]. While HIV control may predict survival over the longer term [31], early death appears to be largely driven by acute illness severity and not markers of HIV control.…”
Section: Discussionmentioning
confidence: 83%
“…27,28 In contrast, in developing settings those figures are lower, reflecting the high rates of late HIV presenters and opportunistic infections commonly seen in those places. 15 Modern ICU standards of care unrelated to HIV therapy (i.e.…”
Section: Impact Of Antiretroviral Therapymentioning
confidence: 99%
“…2,3 The most effective reduction in viral load and restoration of immune function require a combination of antiretroviral drugs. Currently, more than 20 antiretroviral drugs divided into 6 drug classes according to the mechanism of action are used in ART: nucleoside/ nucleotide reverse transcriptase inhibitors (NRTIs), nonnucleoside reverse transcriptase inhibitors (NNRTIs), protease inhibitors (PIs), fusion inhibitors, chemokine receptor 5 antagonists, and integrase strand transfer inhibitors.…”
Section: Antiretroviral Therapymentioning
confidence: 99%
“…In the scenario, the proton pump inhibitor could be replaced by another agent, such as an H 2 Continuing or Stopping ART in the ICU No clear evidence indicates whether an established ART regimen should be continued or stopped when a known HIV-infected patient is admitted to the ICU. 2,3 As previously noted, the risk for drug-drug interactions is marked. However, other issues may also present administration challenges.…”
Section: Art and Drug Interactionsmentioning
confidence: 99%